Development of a functional electrical stimulation cycling toolkit for spinal cord injury rehabilitation in acute care hospitals: A participatory action approach. - Hope Jervis-Rademeyer; Srijana Gautam; Stephanie Cornell; Janelle Khan; Danielle Wilanowski; Kristin E Musselman; Vanessa K Noonan; Dalton L Wolfe; Riccardo Baldini; Steven Kennedy; Chester Ho (PLoS ONE)
The purpose of our study was to develop a toolkit to facilitate the implementation of functional electrical stimulation (FES) cycling for persons with a newly acquired spinal cord injury (SCI) in the acute care inpatient hospital setting. The researchers and community members used participatory action as a research approach to co-create the toolkit. We held two focus groups to develop drafts, with a third meeting to provide feedback, and a fourth meeting to evaluate the toolkit and determine dissemination strategies. Toolkit development followed the Planning, Action, Reflection, Evaluation cycle. We used an iterative design informed by focus group and toolkit consultant (SC) feedback. In focus group discussions, we included FES cycling champions (JK, DW) who led acute care implementation. Focus group members, recruited through purposive sampling, had to 1) have an understanding about FES cycling in acute care for SCI and 2) represent one of these groups: individual living with SCI, social support, hospital manager, clinician, therapist, researcher, and/or acute care FES cycling champion. Twelve individuals took part in four focus groups to develop a toolkit designed to facilitate implementation of FES cycling in SCI acute care in Edmonton, Alberta. Group members included an individual with lived experience, three acute-care occupational or physical therapists, three acute-care hospital managers, and five researchers. Two physical therapists also identified as clinical FES cycling champions. Following an inductive content analysis, we identified four main themes: 1) Health care provider toolkit content and categories, 2) Health care provider toolkit end product, 3) Collaborations between groups and institutions and 4) Infrastructure. Interested parties who utilize FES cycling in acute care for SCI rehabilitation agree that toolkits should target the appropriate group, be acute care setting-specific, and provide information for a smooth transition in care.